ANALISIS SYSTEM POINT OF SALE UNTUK MENINGKATKAN EFISIENSI DAN OPTIMALISASI BISNIS DI TOKO GAURI - Putri Raja, Melantrisna Wuru; Luh Putu Risma Noviana; Ayu Aprilyana Kusuma Dewi (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
This study examines the implementation of a Point of Sale (POS) system at Toko Gauri, a stationery store in Denpasar, to improve operational efficiency and business optimization. Using a qualitative case study, data were collected through observation, interviews, documentation, and questionnaires involving the owner, employees, and customers. The 1–4 Likert-scale questionnaire was analyzed descriptively and supported by one-way ANOVA. Results show the MySIS POS system improves transaction speed, inventory control, and reporting. Employee scores ranged from 3.67 to 4.00, indicating high usability. ANOVA showed a significant difference in customer perceptions (F = 6.198; p = 0.006) based on shopping frequency. The study concludes that POS enhances efficiency and decision-making but requires better integration with non-cash payments like QRIS.